Dexamethasone as an Adjuvant for Caudal Blockade in Pediatric Surgical Patients: A Systematic Review and Meta-analysis. (August 2018) - Chong, Matthew A.; Szoke, Daniel J.; Berbenetz, Nicolas M.; Lin, Cheng
Abstract : BACKGROUND: Caudal block is commonly used to provide postoperative analgesia after pediatric surgery in the lower abdomen. Typically administered as a single-shot technique, 1 limitation of this block is the short duration of analgesia. To overcome this, dexamethasone has been used as an adjuvant to prolong block duration. However, there are concerns about steroid-related morbidity and the optimal route of dexamethasone administration (eg, caudal or intravenous) is unknown. METHODS: We conducted a systematic review and random-effects meta-analysis of randomized controlled trials recruiting pediatric surgical patients receiving a caudal block for surgical anesthesia or postoperative analgesia. Included studies compared dexamethasone (caudal, intravenous, or both) to control. Duration of analgesia was the primary outcome. Database sources were Medline, Embase, the Cochrane Library, and Google Scholar searched up to August 18, 2017, without language restriction. Screening of studies, data extraction, and risk of bias assessment were performed independently and in duplicate by 2 authors. Risk of bias was assessed using Cochrane methodology and the strength of evidence was scored using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. RESULTS: The initial search retrieved 93 articles. Fourteen randomized controlled trials that comprised 1315 pediatric patients met the inclusion criteria. All but 1 study involved lower abdominal operations (orchidopexy, inguinal hernia repair, and hypospadias repair). The caudal and intravenous dose of dexamethasone ranged from 0.1 to 0.2 mg/kg and 0.5 to 1.5 mg/kg, respectively, and all studies were pooled in the main analysis. Dexamethasone prolonged the duration of analgesia by both the caudal route (5.43 hours, 95% confidence interval [CI], 3.52–7.35; P < .001; I 2 = 99.3%; N = 9; n = 620; GRADE quality = moderate) and intravenous route (5.51 hours; 95% CI, 3.56–7.46; P < .001; I 2 = 98.9%; N = 5; n = 364; GRADE quality = moderate) versus control. Secondary benefits of dexamethasone included reduced narcotic rescue analgesia requirement in the postanesthetic care unit (relative risk [RR], 0.30; 95% CI, 0.18–0.51; P < .001; I 2 = 0.0%; N = 5; number needed to treat for benefit [NNTB] = 5; 95% CI, 4–7), less subsequent postoperative rescue analgesia requirement (RR, 0.46; 95% CI, 0.23–0.92; P = .03; I 2 = 96.0%; N = 9; n = 629; NNTB = 3; 95% CI, 2–20; n = 310), and lower rates of postoperative nausea and vomiting (RR, 0.47; 95% CI, 0.30–0.73; P = .001; I 2 = 0.0%; NNTB = 11; 95% CI, 8–21; N = 9; n = 628). Adverse events linked to the dexamethasone were rare. CONCLUSIONS: Caudal and intravenous dexamethasone are similarly effective for prolonging the duration of analgesia from caudal blockade, resulting in a doubled to tripled duration. Given the off-label status of caudal dexamethasone, intravenous administration is recommended—although only high intravenous doses (0.5 mg/kg up to 10 mg) have been studied.